Contrasting levels of student engagement in blended and non-blended learning scenarios - de Brito Lima, Felipe; Lautert, Sintria Labres; Gomes, Alex Sandro (Computers and education, 2021)
The aim of this study is to contrast levels of student engagement in blended and non-blended learning scenarios. The theoretical framework addresses core elements for the implementation of blended learning scenarios and discusses their impacts on student engagement. A design based on the within-subject experimental model was utilized with a sample of 92 tenth grade students from four different groups at a state public secondary school in the Northeast of Brazil. Procedures comprised the application of a survey on familiarity with ICT tools followed by the implementation of two blocks of lessons separated by a two-month interval, each of them composed of computer-assisted blended and traditional lecture-based learning scenarios. Students' responses to the tasks in each lesson were captured through a screen recording application and levels of engagement determined from criteria based on observable quantifiable behaviors. Nonparametric tests show significantly higher levels of student engagement in blended learning scenarios not affected by significant differences in familiarity with ICT. Categories of engagement regarding the students’ use of resources available in the lessons are presented and discussion emphasizes behavioral engagement as a context-specific phenomenon, highlighting implications for teaching practices. •Levels of student engagement in blended and non-blended learning scenarios are contrasted.•Nonparametric tests show significantly higher levels of student engagement in blended learning scenarios.•Engagement was not affected by significant differences in students' levels of familiarity with ICT tools.•Categories of engagement regarding the students' use of the resources available in the lessons are presented.•Discussions emphasize behavioral engagement as a context-specific phenomenon, highlighting implications for teaching practices.